Robust design for 3-DoF anti-windup framework based on QFT. (December 2022) - Mo, Xiaoqin; Zhou, Mi; Wang, Yuan; Lin, Zhen; Li, Zhengqing; Li, Zhongshen
Abstract: On the basis of the fact that all signals in the practical system are always bounded, this paper proposes a practical QFT-based approach for the synthesis of anti-windup compensation for uncertain LTI systems. Meanwhile, a modified version of the circle criterion is developed for saturated systems with parametric uncertainty to reduce the conservativeness of the anti-windup compensator design within the non-interfering anti-windup framework. In the context of QFT, it means enlarging the allowed zone of the compensator remarkably in the Nichols chart compare to the traditional version of the circle criterion. As a result, the less conservative stability boundary provides more room for the compensator synthesis, making the performance improvement possible. Numerical examples demonstrate the effectiveness and the performance improvement as expected of the proposed technique based on QFT for the anti-windup compensator design.